"Gloves Cling to My Hands": A Case Report of Spiny Keratoderma. Issue 6 (November 2017) - Jorge, Emily A.
Abstract : ABSTRACT: Spiny keratoderma is a rare, easily distinguishable variant of punctate keratoderma. It is characterized by a spiny texture with multiple hard keratotic outgrowths on the palms and soles. These spines are likened to an old-fashioned music box but have been labeled by other synonyms such as palmar keratoses, punctate keratoderma, filiform hyperkeratosis, and punctuate porokeratotic keratoderma, to name a few.